Study on the Utilization of Mangrove Forest Plants - Retni S Budiarti; Harlis; Agus Subagyo (Postgraduate, University of Mataram, 2023)
The mangrove forest has unique characteristics, plays a role in ecological and economic functions, and is a natural resource that has not been optimally utilized. This research was conducted in Tungkal 1 Village, Tanjung Jabung Barat Regency, Jambi, to identify the potential utilization of mangrove plants as entrepreneur-based products. The research method involved surveys selected using snowball sampling, interviews with various stakeholders, and data analysis on respondent characteristics, knowledge, understanding, mangrove-based products, community involvement, support, accessibility, and economically valuable strategies for utilizing mangrove plants. The results show that the majority of the community has knowledge about mangrove forests, but their understanding of the potential utilization is still low. Mangrove-based products such as ecotourism, handicrafts, and sustainable fish farming have high economic potential. The level of community involvement in mangrove conservation and support for preservation efforts is high. In conclusion, mangrove management in Tungkal 1 Village can serve as a successful example in supporting sustainable local economic growth while preserving the important